2013
DOI: 10.1002/elan.201200545
|View full text |Cite
|
Sign up to set email alerts
|

Study on Electrochemical Fingerprints and Identification of Different Varieties of Rice and Mouldy Rice by B‐Z Oscillation Reaction System

Abstract: The electrochemical fingerprints of different varieties of rice and mouldy rice were studied by Belousov‐Zhabotinskii (B‐Z) oscillation reaction system with malonic acid as dissipative material under the condition of constant temperature. The results indicated that the chemical composition of rice may influence the kinetic parameters of the B‐Z oscillation reaction, which lead to the electrochemical fingerprint characteristic parameters and the intuitive information changes obviously. The varieties of rice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…y n ), in which x i and y i represent each peak area of the sample fingerprint (SFP) and reference fingerprint (RFP), respectively. The vector cosine of the angle (y) between x and y is defined as qualitative similarity (S F ), which can be calculated using eqn (1). In order to eliminate the situation where large peaks cover up small peaks that are caused by S F , the ratio qualitative similarity S F 0 À Á parameter is defined (eqn (2)).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…y n ), in which x i and y i represent each peak area of the sample fingerprint (SFP) and reference fingerprint (RFP), respectively. The vector cosine of the angle (y) between x and y is defined as qualitative similarity (S F ), which can be calculated using eqn (1). In order to eliminate the situation where large peaks cover up small peaks that are caused by S F , the ratio qualitative similarity S F 0 À Á parameter is defined (eqn (2)).…”
Section: Theorymentioning
confidence: 99%
“…Rice is the seed of monocotyledon Oryza sativa (Asian rice) or Oryza glaberima (African rice). 1 Rice is the finished product of paddy that has been cleaned and hulled. Rice purchased in the market may experience quality issues such as aging and counterfeiting.…”
Section: Introductionmentioning
confidence: 99%
“…27 In 2013, the use of TBAB and PEG as a phase-transfer catalyst was examined for the coupling of heteroaryl bromides with phenylboronic acid mediated by palladium-phosphine acid complexes. 28 Souza and co-workers found that Pd/BaSO 4 (Rosemund's catalyst), a heterogeneous catalyst, allowed the ligand-free synthesis of biaryls with PEG as the solvent and it also enabled recycling of the catalytic system. 29 After studying several solvents (ethanol, H 2 O, PEG-300, and a mixture of PEG-300/H 2 O), the Suzuki-Miyaura of iodobenzene with phenylboronic acid in a mixture of PEG-300/H 2 O using K 2 CO 3 as a base occurred in 100% yield at room temperature and at 80 °C.…”
Section: Scheme 8 Copper-catalyzed Suzuki-miyaura Couplings Of Aryl Imentioning
confidence: 99%
“…The B-Z oscillation chemical reactions have more than twenty elementary reaction steps in the FKN model, so it is a very sensitive system to external chemical substances. 12 The chemical oscillation ngerprints of instant coffee were measured using the B-Z chemical oscillation reaction system. The characteristic redox constituents of different brands or varieties of instant coffee react with oscillation reactants aer adding the coffee sample to the oscillation system, which involves in the consumption and regeneration of HBrO 2 , Br À , Ce 4+ and Ce 3+ .…”
Section: Characteristic Parameters Of Chemical Oscillation Ngerprint...mentioning
confidence: 99%